The Effect of PEO Treatment in a Ta-Rich Electrolyte on the Surface and Corrosion Properties of Low-Carbon Steel for Potential Use as a Biomedical Material - Marcuz, Nádia; Ribeiro, Rafael Parra [UNESP]; Rangel, Elidiane Cipriano [UNESP]; da Cruz, Nilson Cristino [UNESP]; Correa, Diego Rafael Nespeque [UNESP] (MDPI, 2023)
Fe-based materials have extensive applications in the building and automobile industries due to their excellent mechanical properties and low cost. However, their biomedical employment is restricted by the corrosion propensity when in contact with bodily fluids. In this study, single-step Plasma Electrolytic Oxidation, PEO, treatment in Ta-rich electrolyte was used, for the first time, to improve the corrosion resistance of low-carbon steel SAE 1020 for possible use as device implants. The effect of the applied voltage on the chemical and phase composition, topography, wettability, roughness, and corrosion properties were addressed. The results indicated that the Fe-based oxide coatings had a rough and hydrophilic surface, increasing the Ta content with the applied potential. The phase composition of the coatings was mainly composed of hematite (Fe2O3), with the Fourier-transform Infrared Spectroscopy, FTIR, spectrums indicating the presence of some absorbed water and organic molecules. The corrosion resistance of the PEO-treated samples was better than the substrate against saline solution (0.9% NaCl) due to the Fe2O3 growth decorated with Ta particles, especially the sample treated at 200 V. The results state that Ta-enriched Fe-based oxide coatings could significantly improve the applicability of low-carbon steel SAE 1020 as a low-cost biomaterial, particularly for medical devices.
Keywords: corrosion; low-carbon steel; medical devices; PEO; Ta